2019
DOI: 10.3390/biom10010014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allium mongolicum Regel and Its Flavonoids on Constipation

Abstract: Constipation is a common bowel disease in adults with the symptoms of dry stool or difficulty passing stool. Compared with medication therapy, patients show more compliance with the diet therapy, and thus the diet therapy normally exhibits better therapeutic effect. Allium mongolicum Regel s a perennial herb of Liliaceae native to Mongolia, Kazakhstan, and China, which is traditionally used for constipation. In this paper, we partly clarify the effectiveness of A. mongolicum on constipation from two aspects, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Flavonoids have abundant pharmacological activities and biological effects, such as antioxidation, prevention of cardiovascular disease and cancer, and reduction in inflammation [ 11 ], and flavonoids also have therapeutic effects on gastrointestinal disorders. Flavonol naringenin [ 12 ], 7,8-dihydroxyflavone [ 13 ], and Allium mongolicum Regel and its flavonoids [ 14 ] could reverse the symptoms of loperamide-induced constipation in mice. In addition, fermented soymilk with more total isoflavones had better laxative effects than unfermented soymilk [ 15 ], whereas isoflavone-deficient foods could cause constipation while reducing beneficial bacteria and regulating gut microbiota [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have abundant pharmacological activities and biological effects, such as antioxidation, prevention of cardiovascular disease and cancer, and reduction in inflammation [ 11 ], and flavonoids also have therapeutic effects on gastrointestinal disorders. Flavonol naringenin [ 12 ], 7,8-dihydroxyflavone [ 13 ], and Allium mongolicum Regel and its flavonoids [ 14 ] could reverse the symptoms of loperamide-induced constipation in mice. In addition, fermented soymilk with more total isoflavones had better laxative effects than unfermented soymilk [ 15 ], whereas isoflavone-deficient foods could cause constipation while reducing beneficial bacteria and regulating gut microbiota [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory effects of flavonoid-rich fraction of A. ascalonicum (shallot) extract is reported via inducing delayed-type hypersensitivity and TH1 cytokine-IFNγ expression in a mouse model [131]. A. mongolicum extract (100 and 200 mg/kg) containing flavonols (quercetin, kaempferol, and their respective glucosides) has been reported to induce the recovery of fecal excretion and water content while enhancing colon thickness and number of goblet cells in a loperamide (LOP)-induced constipated mouse model [132]. The anti-constipation effects are mediated by the downregulation of aquaglyceroporin-3 (AQP3) expression and up-regulation and activation of G protein alpha (Gα) and phosphoinositide 3-kinases (PI3K) [132].…”
Section: Other Health Benefitsmentioning
confidence: 99%
“…A. mongolicum extract (100 and 200 mg/kg) containing flavonols (quercetin, kaempferol, and their respective glucosides) has been reported to induce the recovery of fecal excretion and water content while enhancing colon thickness and number of goblet cells in a loperamide (LOP)-induced constipated mouse model [ 132 ]. The anti-constipation effects are mediated by the downregulation of aquaglyceroporin-3 (AQP3) expression and up-regulation and activation of G protein alpha (Gα) and phosphoinositide 3-kinases (PI3K) [ 132 ]. Cho et al [ 133 ] reported the protective effects of onion extract (quercetin; 17.1 μM) against radiation-induced cyto- and geno-toxicity in human lymphocytes pertaining to its antioxidant and DNA repair properties.…”
Section: Health Benefits Of Allium Flavonolsmentioning
confidence: 99%
“…Allium mongolicum Regel (AMR), a perennial Liliaceae herb native to Mongolia, Kazakhstan, and China (Inner Mongolia, Gansu, Ningxia, and Xinjiang) [ 1 ] and also known as the Mongolia leek, grows in high-altitude desert steppe and desert areas [ 2 ]. AMR is resistant to wind erosion, drought, and low temperature and is therefore important in preventing wind erosion as well as in maintaining and improving regional ecological environments.…”
Section: Introductionmentioning
confidence: 99%
“…Its leaves are rich in nutrients, possess a unique flavor, and is a natural green uncontaminated food [ 4 ] used to make sauces in cold vegetable dishes and stuffing of steamed stuffed buns and dumplings. In addition, AMR is beneficial in managing functional constipation, helping to maintain colon water content and increasing intestinal transit [ 1 ]. The aqueous extract of AMR has the potential to be used as a functional food or nutraceutical in the prevention and treatment of obesity and hypertension [ 3 ].…”
Section: Introductionmentioning
confidence: 99%